Attendance Information Services Application Based On SMS Gateway As Resource Sharing In SMK Teknologi Plus Padang - Wahyudi, Wahyudi; Putra, Ilham Eka (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2016)
SMK Teknologi Plus Padang has not used computerized systems in data processing student attendance. So, we need an absentee application information can be accessed by carers are easy and quick to help them serving student attendance information. The research method to build these applications through, system development SDLC that stage of system planning, system analysis, system design, and implementation system and thus creating an application that can process student attendance data into information absenteeism in the form of short message SMS that can be easily accessed by guardians of students through mobile devices.